Music Appreciation History, Culture, and Context - Le, Bonnie; Scully, Francis; Edwards, Steven (Open textbook library., 2021)
Music makes us human. Every culture on earth has music. In fact, every human society extending back into prehistoric times has had music. Most of us are surrounded by music. We use it to enhance our mood and to regulate our metabolism, to keep us awake and help us go to sleep, as background to accompany the work, study, exercise, and relaxation that fills our days. But it is precisely when music steps out of this background and asks for our attention, engages our memory and our expectations, that it becomes a fundamentally artistic endeavor. Music is a sonic response to a question that’s not really about sound at all, but rather is historical and social. The study of music is the study of human thought, experience, and history. This course is about the musical imagination. It’s how to think about music, but it’s also about music as a mode of thinking. (inspired by Michael Hays, Professor of Architectural Theory at Harvard University’s Graduate School of Design: Welcome to The Architectural Imagination (edx.org). This textbook was created as part of the Interactive OER for Dual Enrollment project, facilitated by LOUIS: The Louisiana Library Network and funded by a $2 million Open Textbooks Pilot Program grant from the Department of Education. This project supports the extension of access to high-quality post-secondary opportunities to high school students across Louisiana and beyond. This project features a collaboration between educational systems in Louisiana, the library community, Pressbooks technology partner, and workforce representatives. It will enable and enhance the delivery of open educational resources (OER) and interactive quiz and assessment elements for priority dual enrollment courses in Louisiana and nationally. Developed OER course materials will be released under a license that permits their free use, reuse, modification and sharing with others.The target audience for this project and this textbook are dual enrollment students. Dual enrollment is the opportunity for a student to be enrolled in high school and college at the same time. A dual enrollment student receives credit on both their high school and college transcripts for the same course.